The Long Walk : the forced Navajo exile - Denetdale, Jennifer (Chelsea House Publishers, 2008)
Chronicles the events that led to the Navajo Nation's forced removal from their homeland to a reservation in eastern New Mexico in the 1860s, and discusses the lasting impact that relocation had on the Navajo psyche.